Internet Shutdown in Indonesia: An Appropriate Response or A Threat to Human Rights? - Iwan Satriawan; Tareq Muhammad Aziz Elven; Tanto Lailam (Faculty of Law, Sriwijaya University, Indonesia, 2023)
In recent years, there has been an increase in the use of harsh censorship in several parts of the globe, notably Africa and Asia. In some cases, the shutdown may be justified, but in other cases, it is driven by the political interest of the regime. The research evaluates the Internet shutdowns in the post-2019 presidential election in Indonesia and during the social unrest in Papua Island. Using normative legal research, which uses statute, case, and comparative approach concludes that although Internet shutdowns in some situations are tolerable, their usage should be less frequent and more restricted. These explanations must be examined using legality, legitimacy, and proportionality principles to limit official arguments for Internet shutdowns because they infringe on human rights. However, since no enforcement mechanism exists, this is only a formality. The Indonesian government's decision to block Internet access to social media platforms during the 2019 presidential election riots and Papua social unrest is not an appropriate response because the decision violates the principles of declaration, proportionality, necessity, and legality, which must be respected even in an emergency situation. Furthermore, the ruling infringed on the civil rights to information controlled by Article 19 of the ICCPR as adopted by Law Number 12 of 2005. It also harmed several industries, including digital-based commerce. The research proffers alternative Internet policy choices for the government in response to the political escalation and social unrest.